2008
DOI: 10.1097/brs.0b013e3181695d3b
|View full text |Cite
|
Sign up to set email alerts
|

Better Backs by Better Beds?

Abstract: The Waterbed and foam mattress' did influence back symptoms, function and sleep more positively as apposed to the hard mattress, but the differences were small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A medium-firm mattress may be more comfortable because it allows the shoulder and hips to sink in slightly [22]. Bergholdt et al [23] found that the waterbed and the foam mattress seemed superior to the hard mattress, especially when using the probably most relevant "worst case" data. There were no relevant difference between the effects of the water bed and the foam bed.…”
Section: Relationship Between Sleep Habits and Occurrence Of Lbpmentioning
confidence: 99%
“…A medium-firm mattress may be more comfortable because it allows the shoulder and hips to sink in slightly [22]. Bergholdt et al [23] found that the waterbed and the foam mattress seemed superior to the hard mattress, especially when using the probably most relevant "worst case" data. There were no relevant difference between the effects of the water bed and the foam bed.…”
Section: Relationship Between Sleep Habits and Occurrence Of Lbpmentioning
confidence: 99%
“…We assumed that the mattresses might facilitate a better anatomic position because they mould themselves to the exact shape of the body. Another study demonstrated fewer twists from side to side with a polyurethane mattress (Bergholdt et al 2008), which might indicate less-fragmented sleep. However, this was not detected in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Another study demonstrated fewer twists from side to side with a polyurethane mattress (Bergholdt et al . ), which might indicate less‐fragmented sleep. However, this was not detected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included participants with chronic non-specific LBP 41,42,51,53,54,56 (n ¼ 6), chronic non-specific neck pain 44,52,55,58e60 (n ¼ 6), any spinal pain 34e36,61 (n ¼ 4), knee OA 32,40,43,57 (n ¼ 4), general OA 27,33,45 (n ¼ 3), and a combination of people with spinal pain and/or OA 37 (n ¼ 1). All studies classified chronic LBP as pain lasting longer than at least 3e6 months.…”
Section: Participantsmentioning
confidence: 99%
“…ESI included CBT 27,32e37,45 (n ¼ 8), melatonin 42,60 (n ¼ 2), and eszopiclone 41 (n ¼ 1). Other sleep interventions included pillows 43,52,55,58,59 (n ¼ 5), exercise 40,44,53 (n ¼ 3), massage 54,56 (n ¼ 2), singing bowls 61 (n ¼ 1), acupuncture 57 (n ¼ 1), and mattresses 51 (n ¼ 1). Nine studies combined a sleep intervention in addition to a pain intervention: CBT for insomnia with CBT for pain 33,35,37,45 (n ¼ 4), a sleep pharmacological intervention with a pain pharmacological intervention 41,42 (n ¼ 2), pillow with physiotherapy intervention 52,55 (n ¼ 2), and acupuncture for sleep with acupuncture for pain 57 (n ¼ 1).…”
Section: Sleep and Comparison Interventionsmentioning
confidence: 99%